Pengaruh Penerapan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning (PBL) pada Pembelajaran IPA dengan Materi Siklus Air Terhadap Kemampuan Berpikir Kritis Siswa Kelas V SD - Ning Handayani; Endang Widi Winarni; Agus Susanta (UNIB Press, 2024)
This study aims to determine the effect of applying Student Worksheets based on Problem Based Learning on the critical thinking skills in aspects of giving simple explanations and organizing strategies and tactics in fifth grade elementary school students. This research is a quantitative research. The method used is a quasy experiment. The design in this study is The Matching Only Pretest-Posttest Control Group Design. The population in this study were all fifth grade students at SDN 1 Banpres and all fifth grade students at SDN 2 Banpres. The sample in this study were 22 students in class V SDN 1 Banpres as the experimental class and 24 students in class V SDN 2 Banpres as the control class. The instrument given was in the form of a written test consisting of variable aspects of critical thinking skills giving simple explanations as well as aspects of managing strategies and tactics. The results showed that there was a significant effect of the application of Problem Based Learning Student Worksheets on critical thinking skills in the aspect of giving simple explanations as well as aspects of managing the strategies and tactics of class V students at SDN 1 Banpres.